Sustainable Finance and the Global Health Crisis (Taylor & Francis, 2024)
The speed with which the various economies recover from the Covid-19 pandemic will significantly determine the economic pressure placed on the environment in the medium-to-long-term. Furthermore, the pandemic has highlighted the strong interrelations between natural and societal systems, with societal resilience depending on a resilient environmental support system. In this context, the book argues that the pandemic represents a wake-up call for financial systems to be better prepared for the climate crisis and social risk, and has provided a stimulus to scale down the reliance of the global economy on fossil fuels. The first part of the book provides a deep and creative discussion between leading international researchers and experts on the policy options and financial instruments which can help to catalyze the green finance transition in the post-Covid-19 era. The contributions show that sustainable finance is emerging as a powerful tool to advance the transition towards a more environmentally and socially sustainable economic model. Instruments such as sovereign green bonds, green securities, and other sustainability-related securities can play a significant role in the post-Covid-19 world to fund economic stimulus and to lead the way to new and more sustainable future. The second part of the book supports the debate by highlighting a number of selected case studies on financing transitions in different regional contexts including Africa, Asia, Europe, and Latin America. The book marks a significant contribution to the literature on environmental economics and finance, climate change, and sustainability transitions.
English
Keywords: Covid 19,Economy,Pressure,Finance,Risk,Climate Change,Climate Bonds,Green Bonds,Green Bond Market,Green Finance,GHG Emission,EU Gdp,Climate Bonds Initiatives,Green Bond Issuance,EU's Climate,ESG Rating,Sustainability Transition,Teg,Sure,Rec,Circular Economy,Vulnerable Employment,ESG Investment,Green Finance Development,Green Industrial Policies,IFC Performance Standard,Lower Partial Moment,ESG Risk,Pe Mechanism,Sortino Ratio,MERS; thema EDItEUR::K Economics, Finance, Business and Management::KC Economics; thema EDItEUR::K Economics, Finance, Business and Management::KC Economics::KCV Economics of specific sectors::KCVG Environmental economics